Catalyst‐ and Additive‐free Synthesis of α‐Pyrrolyl Amides upon Treatment of α‐Keto Amides with 4‐Hydroxy‐L‐proline. Issue 22 (9th June 2020) - Liu, Guyue; Hao, Feiyue; He, Xiaoyu; Xu, Yan; Jin, Zhengneng; Jiang, Huajiang; Wu, Jiashou
Abstract: A catalyst‐ and additive‐free synthesis of α‐pyrrolyl amides was easily achieved upon treatment of 4‐hydroxy‐L‐proline with α‐keto amides. Broad substrate scope, good functional group tolerance, and operational simplicity are the notable advantages of this protocol. Furthermore, gram‐scale synthesis and further transformation of the resultant products into newly functionalized compounds definitely demonstrated the synthetic utility of this method. Abstract : Treatment of 4‐hydroxy‐L‐proline with α‐keto amides smoothly afforded α‐pyrrolyl amides under catalyst‐ and additive‐free conditions. The developed protocol features the use of commercially available substrates, broad substrate scope, good functional group tolerance, and operational simplicity.